2020
DOI: 10.1016/j.nicl.2020.102415
|View full text |Cite
|
Sign up to set email alerts
|

Structural brain correlates of dementia in Huntington’s disease

Abstract: Highlights Dementia may occur in the early stages of HD and with independence of disease burden. More severe posterior-cortical atrophy is associated with dementia in HD. Neuropsychological alterations of dementia in HD extends beyond executive dysfunction. CAG-independent neuropathological mechanisms may contribute to dementia in HD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 45 publications
6
24
0
Order By: Relevance
“…MoCA global performance correlations analysis demonstrated extensive cortical areas associated with cognitive performance in HD patients. In this sense, our findings are consistent with previous reports in HD that identified specific cognitive deficits –attention, working memory, and executive functions– correlating with cortical changes including cortices of the superior fronto-parietal motor circuits, frontal cognitive control centers, temporal auditory and semantic processing hubs, and occipital visual centers ( Rosas et al, 2005 , 2008 ; Harrington et al, 2014 ; Coppen et al, 2018 ; Martinez-Horta et al, 2020 ). It is important to mention that the MoCA test involves the assessment of several cognitive functions associated with different neurological substrates; therefore, it is understandable that the atrophy of discreet areas within the whole cerebral cortex contributed to the deterioration of MoCA global performance of the HD patients.…”
Section: Discussionsupporting
confidence: 92%
“…MoCA global performance correlations analysis demonstrated extensive cortical areas associated with cognitive performance in HD patients. In this sense, our findings are consistent with previous reports in HD that identified specific cognitive deficits –attention, working memory, and executive functions– correlating with cortical changes including cortices of the superior fronto-parietal motor circuits, frontal cognitive control centers, temporal auditory and semantic processing hubs, and occipital visual centers ( Rosas et al, 2005 , 2008 ; Harrington et al, 2014 ; Coppen et al, 2018 ; Martinez-Horta et al, 2020 ). It is important to mention that the MoCA test involves the assessment of several cognitive functions associated with different neurological substrates; therefore, it is understandable that the atrophy of discreet areas within the whole cerebral cortex contributed to the deterioration of MoCA global performance of the HD patients.…”
Section: Discussionsupporting
confidence: 92%
“…In patients with HD, widespread cortical thinning was observed compared with healthy controls. This pattern of extensive atrophy has been previously reported by our group 7,32 and others 2,4 and shows that the loss of cortical thickness occurs in frontal, temporo-parietal, and occipital cortices in patients with HD. Patients with pre-HD showed no differences compared with healthy controls using stringent statistical thresholds, a fact that has been shown in previous studies in patients with early HD, 33 although others have shown cortical thinning in the early stages.…”
Section: Discussionsupporting
confidence: 88%
“…However, recent works have shown that progressive atrophy of a wide range of cortical regions is linked to the clinical profile of the disease from the early stages. This cortical atrophy involves several regions that participate in cognitive functions such as the precuneus, 5 the anterior cingulate cortex, 6 and the supramarginal, fusiform, and lateral occipital gyrii 7 . The majority of these regions are integral to the functioning of large‐scale cognitive networks, 8 such the salience network (SN) or default‐mode network (DMN).…”
mentioning
confidence: 99%
“…Dementia, associated with several neurodegenerative diseases such as Huntington’s disease (HD), causes genetic defects that decline a patient’s memory, thinking, and emotional state. 6 Tau protein accumulation around brain cells causes the formation of neurofibrillary tangles via amyloid-β protein. Plaques may cause Alzheimer’s disease, or they may be a byproduct of the disease process and related to dementia.…”
Section: Introductionmentioning
confidence: 99%